2006
DOI: 10.1038/sj.ejhg.5201704
|View full text |Cite
|
Sign up to set email alerts
|

Strong linkage on 2q33.3 to familial early-onset generalized osteoarthritis and a consideration of two positional candidate genes

Abstract: A genomewide screen was performed in four extended families with early-onset generalized osteoarthritis (FOA) without dysplasia. The FOA phenotype within these families shows a dominant Mendelian inheritance pattern and may represent common osteoarthritis (OA) at later ages. An initial locus was confirmed by three additional families and refined by 14 markers to a two-point logarithm of odds score of 6.05 (theta ¼ 0.00) for marker D2S155 at chromosome 2q33.3. This locus coincided with the highest multipoint no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 24 publications
1
26
0
2
Order By: Relevance
“…We also analysed the presence of ROA among carriers in the random population as quantitative trait using a sum score of the number of affected joints 16 which revealed similar findings (data not shown).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We also analysed the presence of ROA among carriers in the random population as quantitative trait using a sum score of the number of affected joints 16 which revealed similar findings (data not shown).…”
Section: Discussionmentioning
confidence: 53%
“…16 In brief, significant linkage was observed at 2q33.3 -2q34 between markers D2S1384 and D2S2178 implicating a 5 cM interval (4.6 Mb). 16 Recombinant haplotypes were constructed for all families that contributed positively to the linkage. In families 2 and 4, most affected individuals carry identical heterozygous haplotypes resulting in two possible haplotypes explaining the linkage (Figure 1).…”
Section: Linkage Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…These changes occur most commonly at the bone--cartilage transition line and interestingly, the PTH2R gene is known to be involved in endochondral bone formation [12]. Evidence for linkage of the 2q33 locus, in which the PTH2R gene resides, for familial early--onset generalised osteoarthritis (FOA) has been reported [22]. Although a rare missense mutation in the PTH2R gene (c.786G>T; p.A225S) co--segregating with FOA was discounted as contributing significantly to the FOA phenotype, there was nevertheless evidence of a possible association with generalised radiographic osteoarthritis in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The first genome-wide linkage studies in OA families were published over ten years ago (Leppävuori et al 1999;Loughlin et al 1999). They were followed by a number of twin, sib pair, and family-based studies and their meta-analysis, which together have identified at least fifteen OA loci with a genome-wide significant logarithm of odds score (LOD ≥ 3.3) (Leppävuori et al 1999;Loughlin et al 1999;Ingvarsson et al 2001;Demissie et al 2002;Loughlin et al 2002b;Stefansson et al 2003;Forster et al 2004b;Hunter et al 2004;Southam et al 2004;Greig et al 2006;Lee et al 2006;Mabuchi et al 2006;Meulenbelt et al 2006;Livshits et al 2007;Min et al 2007;Meulenbelt et al 2008). Of these, loci in 2p23-p24, 2q31-q33, 4q31-q32, 7q34-q36, and 19q13 have been implicated also in other independent studies.…”
Section: Genome-wide Linkage Studiesmentioning
confidence: 99%